Changes in Microbiome Activity and Sporadic Viral Infection Help Explain Observed Variability in Microcosm Studies - Pound, Helena L.; Martin, Robbie M.; Zepernick, Brittany N.; Christopher, Courtney J.; Howard, Sara M.; Castro, Hector F.; Campagna, Shawn R.; Boyer, Gregory L.; Bullerjahn, George S.; Chaffin, Justin D.; Wilhelm, Steven W. (Frontiers in Microbiology, 2022)
The environmental conditions experienced by microbial communities are rarely fully simulated in the laboratory. Researchers use experimental containers (“bottles”), where natural samples can be manipulated and evaluated. However, container-based methods are subject to “bottle effects”: changes that occur when enclosing the plankton community that are often times unexplained by standard measures like pigment and nutrient concentrations. We noted variability in a short-term, nutrient amendment experiment during a 2019 Lake Erie, U.S.A. Microcystis spp. bloom. We observed changes in heterotrophic bacteria activity (transcription) on a time-frame consistent with a response to experimental changes in nutrient availability, demonstrating how the often overlooked microbiome of cyanobacterial blooms can be altered. Samples processed at the time of collection (T0) contained abundant transcripts from Bacteroidetes, which reduced in abundance during incubation in all bottles, including controls. Significant biological variability in the expression of Microcystis-infecting phage was observed between replicates, with phosphate-amended treatments showing a 10-fold variation. The expression patterns of Microcystis-infecting phage were significantly correlated with ~35% of Microcystis-specific functional genes and ~45% of the cellular-metabolites measured across the entire microbial community, suggesting phage activity not only influenced Microcystis dynamics, but the biochemistry of the microbiome. Our observations demonstrate how natural heterogenity among replicates can be harnessed to provide further insight on virus and host ecology.